Sembolik oyun testi'nin türkçeye uyarlanması - (:unkn) unknown (My University, 2012)
Araştırmanın amacı; okul öncesi dönem (3-6 yaş) çocukların sembolik oyun oynama davranışlarını ölçecek Sembolik Oyun Testi'nin (Test of Pretended Play) sözel kısmının, geçerlik ve güvenirlik çalışmasının yapılmasıdır. Sembolik Oyun Testi Vicky Lewis ve Jill Boucher tarafından 1997'de geliştirilmiştir. Test 1 ila 6 yaş arasında normal gelişim gösteren çocuklar ile 8 yaşa kadar olan gelişimsel olarak sorun yaşayan çocukların sembolik oyun gelişimlerini ölçmek amacıyla düzenlenmiştir. Testin sözel olan ve sözel olmayan iki kısmı vardır. Sözel kısmı dört alt bölümden oluşmaktadır. Bunlar; günlük nesneler, oyuncaklar ve temsili olmayan materyaller, temsili tek oyuncak, tek başına sembolik oyun oynaması şeklindedir. Güvenirlik çalışmasında test-tekrar test korelasyonu ,933 (p<,001) olarak bulunmuştur. Bu araştırmada ölçeğin geçerlik çalışması için, yapılan istatistiksel analizler sonucunda Sembolik Oyun Toplam Puanları ile Raven Progressif Matriks Testi (RAVEN) toplam puanları arasında istatistiksel açıdan, 001 düzeyinde, Ankara Gelişimsel Tarama Envanteri (AGTE) ile, 001 düzeyinde, Dil Kullanım Ölçeği ile, 001 düzeyinde pozitif yönde anlamlı ilişkiler elde edilmiştir. Normal gelişim gösteren, otistik ve zihin engelli çocukların sembolik oyun, soyut düşünce, gelişim ve dil kullanım becerileri açısından karşılaştırmaları için, ortalamalar arasındaki farklılıklar incelendiğinde; normal gelişim gösteren grubun puan ortalamasının otistik ve zihin engelli gruptan; zihin engelli grubunun ortalamalarının da, otistik gruptan anlamlı derecede yüksek olduğu görülmüştür.

The objective of present research is to conduct validity and reliability analysis of the verbal section of Test of Pretended Play that will measure pretended play behaviors of pre-school age children (3-6 years of age). Test of Pretended Play was first developed by Vicky Lewis and Jill Boucher in 1997. This test aimed to measure pretended play behavioral development of normal children between ages 1 to 6 besides children with mental developmental problems till the age 8. The test consists of two parts; verbal and nonverbal. Verbal part is composed of four subsections which are daily objects, toys and non-representative materials, one-symbol toy, playing pretended play alone. Reliability analysis demonstrated that test-retest correlation is ,933 (p<,001). In present research, at the end of statistical analyses conducted to detect the validity analysis of scale, a statistically meaningful positive relationship on level ,001 has been detected between Pretended Play Total Scores and Raven Progressive Matrix Test (RAVEN) total; a statistically meaningful positive relationship on level ,001 with Ankara Developmental Screening Inventory (ADSI) and a statistically meaningful positive relationship on level, 001 with Language Use Scale. In order to compare with respect to pretended play normally developing children and children with autism and mental disability, abstract thinking, development and language use skills as the differences between total average scores are analyzed, it surfaces that score average of normally developing children is higher than children with autism and mental disability; score average of children with mental disability is on the other hand significantly higher than autistic group.
Turkish adaptation of test of pretended play
Keywords: Eğitim, Eğitim Araştırmaları